Correction: Microwave-assisted palladium-catalysed isonitrile insertion in 2-bromophenylureas for efficient synthesis of 4-substituted imino 4H-benzo[d][1, 3]oxazin-2-amines. Issue 38 (27th March 2015) - Pandey, Garima; Batra, Sanjay
Abstract : Correction for 'Microwave-assisted palladium-catalysed isonitrile insertion in 2-bromophenylureas for efficient synthesis of 4-substituted imino 4 H -benzo[ d ][1, 3]oxazin-2-amines' by Garima Pandey et al., RSC Adv., 2015, 5, 28875–28878.